Substance Abuse Behaviour Among Youths: The Predictive Effects of Social Media and Peer Pressure - Odumodu N., Constance; Emmanuel E, Uye; Roberts, Enyelunekpo (Program Studi Psikologi Islam (IAIN) Kediri, 2024)
Substance abuse behaviour has caused harm to individuals, families and the larger society. Studies linking social media and peer pressure to substance abuse behaviour among youths in Rivers State are scarce. Therefore, this study investigated social media and peer pressure as predictors of substance abuse behavour among youths in Ahoada-East and Port Harcourt metropolis. Cross-sectional survey design was adopted while data were collected from 234 participants using validated scales. Data were analyzed using multiple regression and independent samples t-test to test two hypotheses at p =.001 level of significance. The result revealed that social media and peer pressure jointly predicted substance abuse behaviour among study participants (R2 = .730, F= 6.724, p =.001). Further result showed that peer pressure independently predicted substance abuse behaviour among youths in the study samples (β-= -.147, t = -2.088, p = .026) while social media did not (β = -.841, t = -1.118, p > .05). It is concluded that social media and peer pressure are good predictors of substance abuse behaviour. Therefore, the study concluded that parents, governmental agencies and other stakeholders should work in unison to reduce factors that increase substance abuse behaviour among youths in the study population.